The microdynamics of social regulation: Comparing the navigation of disagreements in text-based online and face-to-face discussions. (September 2020) - Roos, Carla A.; Postmes, Tom; Koudenburg, Namkje
This study explores how people navigate the field of tension between expressing disagreement and maintaining social relationships in text-based online as compared to face-to-face discussions. In face-to-face discussions, differences of opinion are socially regulated by introducing ambiguity in message content coupled with instant responding on a relational level. We hypothesized that online messages are less ambiguous and less responsive, both of which may hinder social regulation. Thirty-six groups of three unacquainted students discussed politically controversial statements via chat, video-chat (nonanonymous), and face-to-face, in a multilevel repeated measures Graeco-Latin square design. Content coding revealed that online discussions were relatively clear and unresponsive. This related to participants experiencing reduced conversational flow, less shared cognition, and less solidarity online. These results suggest that ambiguity and responsiveness enable people to maintain social relationships in the face of disagreement. This emphasizes the key role that subtle microdynamics in interpersonal interaction play in social regulation.